Archaeobotany of Great Zimbabwe - (:unkn) unknown (My University, 2023)
The archaeobotanical record from Zimbabwe includes charred remains from Early Holocene through to Iron Age sites, often recovered by dry-sieving soil samples (Jonsson, 1998). More focused efforts to recover archaeobotanical macrofossils at Iron Age sites have been conducted at Great Zimbabwe (Jonsson, 1998; Chikumbirike, et al. 2016) and Mtanye (Mushangwe, 2019). However, systematic flotation of samples has largely been absent, and we lack detailed information about the plants present throughout the occupation of sites.As part of the project, ‘Archaeometry and social formation in southern Africa’, led by Professor Shadreck Chirikure, we are undertaking excavations at the iconic World Heritage site of Great Zimbabwe. We will systematically sample contexts for macrobotanical remains using flotation methods and analyse microbotanical remains from soil samples. We will also collect modern flora and seed samples from locally grown plants for morphometric and isotopic comparison with archaeobotanical materials. As there has been relatively little archaeobotanical data published from Great Zimbabwe or other contemporary archaeological sites, our first objective is to build a clear understanding of the plant species present during the occupation of the site. We will then ask broader questions about the social and environmental context of plant use at the site and link with the archaeozoological and material records also being investigated as part of the project.In this poster, we summarise the existing archaeobotanical data from across Zimbabwean archaeological sites before discussing our archaeobotanical plans for excavation at Great Zimbabwe.Chikumbirike, J., Bamford, M. K., Esterhuysen, A. B. (2016). A Study of Archaeological Charcoal from Great Zimbabwe. The South African Bulletin, 71(204), pp107-118.Jonsson, J. (1998) Early Plant Economy in Zimbabwe. Studies in African Archaeology 16. Department of Archaeology and Ancient History, University of Uppsal
Keywords: African Research